2015
DOI: 10.3758/s13414-015-0916-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceived foreign accentedness: Acoustic distances and lexical properties

Abstract: In this study, we examined speaker-dependent (acoustic) and speaker-independent (lexical) linguistic influences on perceived foreign accentedness. Accentedness ratings assigned to Chinese-accented English words were analyzed, taking accentedness as a continuum. The speakerdependent variables were included as acoustic distances, measured in relation to typical native-speaker values. The speakerindependent variable measures were related to the properties of individual words, not influenced by the speech signal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…In recent years, generalized additive modelling (GAM) has gained popularity and has been applied to a variety of different linguistic data such as modelling reaction times (Baayen, 2010), event-related potentials (Tremblay & Newman, 2015), accentedness ratings (Porretta et al, 2015) and dialectal variation (Wieling et al, 2014), among others. In addition to this, GAM has been extensively used in ecology (see Zuur et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, generalized additive modelling (GAM) has gained popularity and has been applied to a variety of different linguistic data such as modelling reaction times (Baayen, 2010), event-related potentials (Tremblay & Newman, 2015), accentedness ratings (Porretta et al, 2015) and dialectal variation (Wieling et al, 2014), among others. In addition to this, GAM has been extensively used in ecology (see Zuur et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The results show that gradiently foreign-accented words result in differences in the strength with which they prime the intended lexical item. Previous work (Munro, 1993;Porretta et al, 2015) has shown that acoustic dimensions, taken as distances from typical native productions, influence ratings of foreign accentedness. This has been understood as a goodness-of-fit judgment between the token and the representation of an acceptable native production.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these, List (i.e., counterbalance with four levels), Trial, and Log frequency of the target word (from COCA, Davies, 2008) were included, along with random effects for Subject and Item. As stated above, mean accentedness ratings for each item were obtained from Porretta et al (2015). These ratings served as a measure of accentedness associated not only with each talker but with each experimental item allowing for a more fine-grained investigation of the effect of accentedness.…”
Section: Rt Model -The Effect Of Accentedness and Experiencementioning
confidence: 99%
See 2 more Smart Citations